2024
DOI: 10.3847/2041-8213/ad1ced
|View full text |Cite
|
Sign up to set email alerts
|

Where Did the Amaterasu Particle Come From?

Michael Unger,
Glennys R. Farrar

Abstract: The Telescope Array Collaboration recently reported the detection of a cosmic-ray particle, “Amaterasu,” with an extremely high energy of 2.4 × 1020 eV. Here we investigate its probable charge and the locus of its production. Interpreted as a primary iron nucleus or slightly stripped fragment, the event fits well within the existing paradigm for UHECR composition and spectrum. Using the most up-to-date modeling of the Galactic magnetic field strength and structure, and taking into account uncertainties, we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…2 Just before the present paper was finished, a set of new regular GMF models was released [20]. Using results from another recent paper of the same authors [21] we estimated the magnitude of UHECR deflection in new models at the position of the highest energy TA event to be maximum a factor 1.3 of the deflection in JF12 GMF model. Using this estimation with our expected flux maps we found that the p-value for proton is less than 1% for new GMF models too.…”
Section: Uhecr Correlation With Lss For Various Primary Typesmentioning
confidence: 99%
“…2 Just before the present paper was finished, a set of new regular GMF models was released [20]. Using results from another recent paper of the same authors [21] we estimated the magnitude of UHECR deflection in new models at the position of the highest energy TA event to be maximum a factor 1.3 of the deflection in JF12 GMF model. Using this estimation with our expected flux maps we found that the p-value for proton is less than 1% for new GMF models too.…”
Section: Uhecr Correlation With Lss For Various Primary Typesmentioning
confidence: 99%